Comparative distribution and population genetics of bisexual and parthenogenetic Asian longhorned tick (Haemaphysalis longicornis) in the Republic of Korea - Jiseok Kim; Donghun Kim (Ticks and Tick-Borne Diseases, 2025)
The Asian longhorned tick (Haemaphysalis longicornis) is an ectoparasite that transmits several pathogens, including severe fever with thrombocytopenia syndrome virus, to humans and animals. Wild populations of H. longicornis are maintained by both bisexual and asexual reproductive strategies. This study examined the geographical distribution and genetic differentiation of bisexual and parthenogenetic H. longicornis populations collected from 12 cities across the Republic of Korea: Chuncheon (CC), Sokcho (SC), Samcheok (SCH), Ganghwa (GH), Sangju (SJ), Ulsan (US), Jinju (JNJ), Boryeong (BR), Gochang (GC), Jindo (JD), Jeju (JJ), and Seogwipo (SG). Based on 16S ribosomal DNA sequence analysis, parthenogenetic and bisexual individuals were found to coexist at varying proportions depending on the region. Parthenogenetic individuals were more dominant in the northeastern regions (CC, US, SJ, SC, GH, and SCH), while bisexual individuals were more abundant in the southwestern regions (SG, BR, JD, JJ, GC, and JNJ). Population genetic analysis based on concatenated mitochondrial cytochrome c oxidase subunit I (COI) and cytochrome B (CytB) genes revealed that the genetic structure of female ticks was primarily influenced by their reproductive strategy (bisexual or parthenogenetic), rather than by geographic origin. Demographic analysis detected evidence of population expansion in both northeastern (CC, SC, and SCH) and southwestern (JD and SG) regions. These findings enhance the understanding of H. longicornis population dynamics in the Republic of Korea.